Effects of metallic silicon on the synthsis of β-SiC Powders by a Carbothermal Reduction Using SiO2-C hybrid precursor fabricated by a Sol-gel process - Jo, Y.-C.; Youm, M.-R.; Yun, S.-I.; Cho, G.-S.; Park, S.-W. (2013)
The objective of this study was to develop a synthesis process for β-SiC powders to reduce the synthesis temperature and to control the particle size and to prevent particle agglomeration of the synthesized β-SiC powders. A phenol resin and TEOS were used as the starting materials for the carbon and Si sources, respectively. SiO2-C hybrid precursors with various C/Si mole ratios were fabricated using a conventional sol-gel process. β-SiC powders were synthesized by a carbothermal reduction process using SiO2-C hybrid precursors with various C/Si mole ratios (1.6 ~ 2.5) fabricated using a sol-gel process. In this study, the effects of excess carbon and the addition of Si powders to the SiO2-C hybrid precursor on the synthesis temperature and particle size of β-SiC were examined. It was found that the addition of metallic Si powders to the SiO2/C hybrid precursor with excess carbon reduced the synthesis temperature of the β-SiC powders to as low as 1300°C. The synthesis temperature for β-SiC appeared to be reduced with an increase of the C/Si mole ratio in the SiO2-C hybrid precursor by a direct carburization reaction between Si and excess carbon. ？ 2013 The Korean Ceramic Society.
Keywords: Direct carburization; Hybrid precursor; Metallic silicon; Particle agglomerations; Powder synthesis; SiC; Synthesis process; Synthesis temperatures; Carbon; Carbothermal reduction; Fabrication; Particle size; Powders; Silicon; Silicon oxides; Sol-gel process; Synthesis (chemical); Silicon carbide